Culture, Politics and Governing - Nickel, P. author. aut Link
VIII, 191 p.
Keywords: Culture, Politics, and Governing: The Contemporary Ascetics of Knowledge Production is a critical, interdisciplinary approach to how the practices that govern the production of knowledge and culture have material consequences for how we experience everyday life.